Development strategy of rice farming in coastal area of Maros Regency. Issue 1 (April 2020) - Amrullah, A; Saadah; Darwis; Ibrahim, T; Busthanul, N; Bulkis, S; Dzulhajrah, A S; Putri, D A
Abstract: This study aims to formularize the strategy of developing rice farming in Maros Regency. A sampling of the study area used the census method by taking the entire population into a sample of 23 farmers who were members of the Pajalayya Baru Farmer Group and key informants as many as two people consisting of village officials and extension workers. The results showed that the rice farming development strategy that could be applied in Kuri Caddi Hamlet, Maros Regency, namely utilizing labor to cultivate land given to farmers, proposed agricultural technology such as tractors, threshing machines, seeds, fertilizers with the support of farmer groups, improving the quality of human resources with become an active member of the Farmers Group, conducting comparative studies in areas with more advanced agriculture, carrying out mitigation actions such as maintaining the stability of the coastline, maintaining the balance of nature, not destroying coral reefs on the coast, making new innovations to develop farming, and cooperating with farmer shops to procurement of agricultural inputs.